h → 0 lim h 1 ∫ 3 − h 3 + h x 2 + 1 4 x − 2 d x = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
L = h → 0 lim h 1 ∫ 3 − h 3 + h x 2 + 1 4 x − 2 d x = h → 0 lim h 1 ∫ 3 3 + h x 2 + 1 4 x − 2 d x + h → 0 lim h 1 ∫ 3 − h 3 x 2 + 1 4 x − 2 d x = d x d ∫ 3 3 + h x 2 + 1 4 x − 2 d x + d x d ∫ 3 − h 3 x 2 + 1 4 x − 2 d x = x 2 + 1 4 x − 2 ∣ ∣ ∣ ∣ x = 3 + x 2 + 1 4 x − 2 ∣ ∣ ∣ ∣ x = 3 = 1 + 1 = 2
This question can be easily solved by using two important methods namely, use of L'hospital rule for limits and another one being DUIS i.e. Differentiation Under Integral Sign. As we have integration with limits 3+h and 3-h with h tending to 0, so numerical value of integration tends to 0, So this is case of 0/0, and so to evaluate the value of limits we can use L'hospital rule, which then requires DUIS in the numerator(need not to say that denominator becomes 1 after differentiation).
Problem Loading...
Note Loading...
Set Loading...
Let f ( t ) = ∫ 3 t x 2 + 1 4 x − 2 d x . Then f ′ ( t ) = t 2 + 1 4 t − 2 and it is continuous at any real number.Then the limit in the question can be written like this L = h → 0 lim h f ( 3 + h ) − f ( 3 − h ) . Now applying L'Hopital 's Rule and using the continuity of f ′ we get L = h → 0 lim ( f ′ ( 3 + h ) + f ′ ( 3 − h ) ) = 2 f ′ ( 3 ) = 2